Best One-Sided Multiplier Approximation of Unbounded Functions by Trigonometric Polynomials - Falih, Raad; K. A-Saidy, Saheb; J. Al-Jawari, Naseif (Al-Nahrain Journal of Science, 2021)
The purpose of this paper is to find the best one – sided multiplier approximation of unbounded functions in – space by trigonometric polynomials. Also, we will estimate the degree of the best one – sided multiplier approximation in term of averaged modulus.